Crazy rich families in Singapore: Property, trust and business disputes, and the incompatibility of English Principles - YIP, Man (Institutional Knowledge at Singapore Management University, 2022)
High net-worth (and sometimes high-profile) families in Singapore continue to face internal disputes. These disputes sometimes lead to litigation about matters relating to trusts, estates, family companies and, increasingly, mental capacity issues. This paper will discuss some recent developments in Singapore in relation to family wealth disputes. They will particularly consider cases relating to mental capacity, jointly owned property and family businesses and companies.